Breaking Cocoa, Trinidad - (:unkn) unknown (My University, 2009)
The labourers break the pods and extract the cocoa beans. On the ground and in the baskets are the beans that are still encased in their white fleshly meat. The postcard is addressed to Mrs. Richardson, Rockhampton, Glosshire. The postcard is postmarked May 14th, 1909.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa trade--Trinidad and Tobago; Agriculture--Trinidad and Tobago; 1909; Cocoa--Trinidad and Tobago; Cocoa processing--Trinidad and Tobago; Working class--Trinidad and Tobago